1999
DOI: 10.1359/jbmr.1999.14.5.810
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineralization and Turnover in Preterm Infants at 8–12 Years of Age: The Effect of Early Diet

Abstract: Our previous studies raised two hypotheses: first that suboptimal early nutrition and second that human milk have enhancing effects on long-term bone mineralization. To test these hypotheses experimentally, we measured whole body and regional bone mineral content (BMC) and bone mineral density (BMD), using dual-energy X-ray absorptiometry and single-photon absorptiometry, and bone turnover at 8-12 years in 244 preterm children (128 boys) who participated in a prospective randomized study of diet during the neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
71
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(78 citation statements)
references
References 33 publications
(40 reference statements)
5
71
1
1
Order By: Relevance
“…In humans, this appears to be the case for ischaemic heart disease, diabetes mellitus and hypertension (Barker, 1993). It appears likely to apply to bone also as we, and others, have previously reported early life associations with smoking in utero and breast-feeding in early life (Jones et al, 2000a,b;Backstrom et al, 1999) as well as breast milk supplementation, although the bene®t reported at age 5 y did not persist at age 11 y (Bishop et al, 1996;Fewtrell et al, 1999). The dietary associations we report in this paper are independent of these factors and, unlike both breast-feeding and smoking, are present in both term and preterm infants, suggesting that they are not dependent on a possible physiology of maturity.…”
Section: Discussionmentioning
confidence: 65%
“…In humans, this appears to be the case for ischaemic heart disease, diabetes mellitus and hypertension (Barker, 1993). It appears likely to apply to bone also as we, and others, have previously reported early life associations with smoking in utero and breast-feeding in early life (Jones et al, 2000a,b;Backstrom et al, 1999) as well as breast milk supplementation, although the bene®t reported at age 5 y did not persist at age 11 y (Bishop et al, 1996;Fewtrell et al, 1999). The dietary associations we report in this paper are independent of these factors and, unlike both breast-feeding and smoking, are present in both term and preterm infants, suggesting that they are not dependent on a possible physiology of maturity.…”
Section: Discussionmentioning
confidence: 65%
“…Our preterm infants seemed to have normal BMD and BMC compared with the age-and height-matched control group at 4 y of age, which contradicted our initial hypothesis. Ex-preterm infants and adults have lower bone mass (2-5) than full-term controls, although other studies have found that the bone mass in ex-preterm infants either is appropriate for their body size or does not differ from normal-weight full-term infants (7,8,11). These findings might reflect different treatment strategies in modern neonatal intensive care units.…”
mentioning
confidence: 93%
“…Many studies have found that ex-preterm infants are shorter, lighter, and have lower bone mass (2-5) than their full-term peers, and ex-preterm infants who are small for gestational age at birth seem to have the most risk (6). However, several studies have found that the bone mass in ex-preterm infants is appropriate for their body size (7,8) and one study proposed that bone mineral density (BMD) in very-low-birth-weight infants is normalized at 2 y of age (9). During adolescence, children who were born prematurely do not have different bone mineral content (BMC ) (10) or BMD (11) (adjusted for height and weight) in comparison with normal-weight children born at full term.…”
mentioning
confidence: 99%
“…Long-term data show that the neonatal period is critical in terms of the effects of nutrition on later health and developmental outcomes. [9][10][11][12] The first year of life may provide an important opportunity for human somatic and brain growth to compensate for earlier deprivation. A key question is whether VLBW infants have special nutritional requirements in the postdischarge period and, in more biologic terms, whether this period of nutrition is also critical for later health and development, particularly since it is common for human milk fortifiers to be stopped and/or term infant formulae to be substituted at an arbitrary time point, at hospital discharge.…”
Section: Introductionmentioning
confidence: 99%